Christianity Maidservant to War? - Denton-Borhaug, Kelly; Joseph, Simon J. 1966-; Hauerwas, Stanley 1940- (2016)
In this multi-book review article, the author examines three new texts that make the case for a deeper, richer understanding of the Christian tradition of nonviolence. All three authors argue that traditions of nonviolence, and misgivings and suspicion regarding the sanctioned shedding of blood, are central to the understanding and practice of Christianity, and deserve to be taken more seriously by researchers and practitioners alike.
Keywords: Christianity; Ethics; Just War; Nationalism; Nonviolence; Sacrifice; Rezension